Successful treatment of multi-focal XDR tuberculous osteomyelitis - Abeer N. Alshukairi; Abdulrahman A. Alrajhi; Abdulfattah W. Alamri; Adel F. Alothman (Elsevier, 2016)
Summary: We herein describe the nosocomial transmission of a pre-XDR or MDR case of pulmonary tuberculosis in a HIV-negative health care worker in an area endemic for MDR and XDR tuberculosis. Following inadequate therapy and non-compliance, he presented with extra-pulmonary XDR tuberculosis in the form of multi-focal osteomyelitis and encysted pleural effusion. He was cured after two years of treatment with various anti-tuberculous drugs in addition to interferon gamma. Keywords: XDR tuberculosis, Osteomyelitis, Therapy